2003
DOI: 10.1021/jf026227q
|View full text |Cite
|
Sign up to set email alerts
|

Application of Microwave Energy in the Manufacture of Enhanced-Quality Green Tea

Abstract: Green tea manufacture was standardized with respect to the inactivation of polyphenol oxidase (PPO), rolling, and drying for quality manufacture. Inactivation of PPO by parching, steaming, microwave heating, and oven heating was monitored in tea shoots. The inactivated shoots were rolled under regimens of high and low pressures and dried by microwave heating, oven heating, or sun-drying; total phenols and catechins were estimated. Parched and sun-dried teas contained the lowest levels of total phenols and cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 8 publications
1
35
0
1
Order By: Relevance
“…It has been reported that microwave drying has the ability to inactivate PPO because microwaves inhibit the binding of polyphenols to the leaf matrix. [15] Microwave inactivation of PPO has been used in the manufacture of green tea. In microwave treatment, the absorption of microwave energy by water molecules in the plant samples is rapid, and inactivation of degradative enzymes is faster compared to the conventional oven.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…It has been reported that microwave drying has the ability to inactivate PPO because microwaves inhibit the binding of polyphenols to the leaf matrix. [15] Microwave inactivation of PPO has been used in the manufacture of green tea. In microwave treatment, the absorption of microwave energy by water molecules in the plant samples is rapid, and inactivation of degradative enzymes is faster compared to the conventional oven.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Xu and Chen [11] reported that gallated catechins usually convert into non-gallated catechins through hydrolysis under humid and heating conditions. Gulati [12] also reported that the chemical content and the composition of green tea catechins may vary with the conditions of processing. Reduction in the EGCG content at longer steaming duration therefore could be as a result of the release of EGC from EGCG.…”
Section: Discussionmentioning
confidence: 99%
“…Higher values of catechin and polyphenol in green tea were also found when using the microwave technique compared with kiln drying. [23] NIR spectroscopy Prediction of moisture content based on NIR PLS models for moisture content quantification of the samples (leaves/sticks and leaves) were developed separately, correlating the spectral data with the reference values obtained by the official method (kiln) and the values obtained by microwave. The best models were evaluated based on different pretreatments, number of latent variables, and on the verification of anomalous samples.…”
Section: Operational Parameters For Microwave Dryingmentioning
confidence: 99%